'That's not necessarily for them': LGBTIQ+ young people, social media platform affordances and identity curation. (November 2019) - Hanckel, Benjamin; Vivienne, Son; Byron, Paul; Robards, Brady; Churchill, Brendan
Lesbian, gay, bisexual, transgender, queer, intersex, and other non-heterosexual and gender diverse (LGBTIQ+) young people utilise a range of digital media platforms to explore identity, find support and manage boundaries. Less well understood, however, is how they navigate risk and rewards across the different social media platforms that are part of their everyday lives. In this study, we draw on the concept of affordances, as well as recent work on curation, to examine 23 in-depth interviews with LGBTIQ+ young people about their uses of social media. Our findings show how the affordances of platforms used by LGBTIQ+ young people, and the contexts of their engagement, situate and inform a typology of uses. These practices – focused on finding, building and fostering support – draw on young people's social media literacies, where their affective experiences range from feelings of safety, security and control, to fear, disappointment and anger. These practices also work to manage boundaries between what is 'for them' (family, work colleagues, friends) and 'not for them'. This work allowed our participants to mitigate risk, and circumnavigate normative platform policies and norms, contributing to queer-world building beyond the self. In doing so, we argue that young people's social media curation strategies contribute to their health and well-being.